Deskripsi Kesalahan Siswa dalam Menyelesaikan Soal Matematika Berbasis PISA pada Konten Change and Relationshi - Djadir; Awi; Sulhijrah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This research was conducted to find out the description of the kind of mistakes made by students in solving mathematics problems based on PISA on Change and Relationship content in terms of the initial capability that was adapted from Newman's error analysis. This research is qualitative research with descriptive approach involves the subject as much as 6 students of class IX selected based on the value of mathematics and the recommendation of the teacher. The research instrument using 4 grains of math problems based on PISA devoted to the content change and relationship and the interview. The results of the research showed that: (1) Students with high mathematics skills are perform the type of transformation error, process skill, and encoding; (2) Students with medium mathematics skills are performing the type of transformation error, process skill, and encoding; and (3) Students with low mathematics skills are performing the type of comprehension, transformation, process skill, and encoding error.